2012
DOI: 10.1071/ah11059
|View full text |Cite
|
Sign up to set email alerts
|

Safe timing for an urgent Caesarean section: what is the evidence to guide policy?

Abstract: Urgent CS should occur as soon as possible, but there is insufficient evidence to support a definite time frame, such as 30 min. A consistency of approach and nomenclature in describing the urgency of CS is necessary, which would enable criteria for further audit regarding DDI. Staff training should be addressed to improve transfer systems for CS. Antenatal risk assessment and congruence with role delineation and service delivery capacity is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…There are studies that have found that a DDI ≤75 minutes is an achievable target and neonatal outcomes are not significantly worse if 75 minutes are not exceeded. [7,16,28] The study by le Riche et al [21] found a median DDI of 48 minutes for Category 1 CS, within the 75-minute benchmark. The median DDI achieved in our study was 75 minutes, i.e.…”
Section: Table2 Characteristics Of the Study Population According To Ddi Subgroupsmentioning
confidence: 94%
“…There are studies that have found that a DDI ≤75 minutes is an achievable target and neonatal outcomes are not significantly worse if 75 minutes are not exceeded. [7,16,28] The study by le Riche et al [21] found a median DDI of 48 minutes for Category 1 CS, within the 75-minute benchmark. The median DDI achieved in our study was 75 minutes, i.e.…”
Section: Table2 Characteristics Of the Study Population According To Ddi Subgroupsmentioning
confidence: 94%